Finite element analysis of cold-formed steel structural members with different arrangement of perforations - Nur Idayu, Ibrahim (2017)
An investigation of cold-formed steel section subjected to compression loading was undertaken using Finite Element Analysis. The most accurate approach to understand the behaviour of cold-formed steel sections with different arrangement of perforations is done by laboratory testing. However, laboratory testing is expensive and take a long time. The development of numerical analysis, modeling and analysing using Finite Element Analysis software is another alternative that can eliminate the expensive and time taking by laboratory testing. Thus, Finite Element Analysis was used for this study to modeling and analysing the cold-formed steel column as example, previous researcher also stated that Finite Element Analysis can predict the buckling mode (M.P. Kulatunga et. al., 2013). The objectives was to study the effect of perforations having different arrangement of perforations together to analyse the stress-strain behaviour and buckling behaviour. For this purpose, finite element model was developed using LUSAS 14.0 software which having circular perforations with height of specimen used was; 600 mm for short, 1500 mm for intermediate, and 2000 mm for slender and thickness used was 1.6 mm. Each height of specimen contain seven specimens which one of it without perforation and six of them having three perforations with different arrangement of perforations position. Fixed and pinned ended support was assigned to validate the Finite Element Analysis. Each model was subjected to load at the bottom of the column. The type of meshing used was QSL8 for each specimen. The simulation that involved in this Finite Element study is linear analysis and linear buckling analysis. The result that obtained from the analysis was deformed mesh, stress maximum, strain maximum, displacement, buckling behaviour, and buckling load. The results of the study shows the strength of column greatly varied with the perforation position. It shows that the cold-formed steel column without perforation is stronger in strength but it had the local buckling. For the cold-formed steel column with perforations, the strength of column will be reduced a bit by the perforations but it had many advantages. The perforations is important to accommodate plumbing, electrical and heating services to the walls and ceilings of the buildings and perforations can stop the local buckling from occur in the column. In conclusion, cold-formed steel column with perforations can be used in construction but it need to be design with the best performance.